Mergers, acquisitions, and strategic alliances as collaborative methods of strategic development and change - Gomes, Emanuel (2022)
This overview article briefly discusses the importance and implications of collaborative methods of development. It provides an overview of the various alternative collaborative methods available and highlights the main critical success factors associated with the management of the strategic change processes which these often are. While providing an overview of each paper, this article highlights the importance of a multi-disciplinary approach and highlights the interconnectedness between a variety of factors and their performance implications. To conclude, avenues for further research are suggested to further strengthen the view of a more pluralistic, multi-disciplinary, multi-phasic, and interconnected approach to external collaborative methods of development.